ANALISIS EMPLOYEE ENGAGEMENT DAN JOB SATISFACTION TERHADAP TURNOVER INTENTION KARYAWAN PADA UMANA BALI, LXR HOTELS & RESORTS - NYOMAN DAKSA NANDANA (GANEC SWARA, 2024)
This study aims to determine between the variables of Employee engagement and Job Satisfaction, partially or simultaneously on Turnover Intention.  In this study, the population is all employees of Umana Bali, LXR Hotels & Resorts, totaling 245 employees. Data collection from samples was carried out using a cross-sectional design method by distributing online questionnaires in the form of google forms. Sampling technique using Proportionate Stratified Random Sampling technique. So that the sample used in this study amounted to 72 respondents. This type of research uses explanatory research with a quantitative approach. This research analysis is processed using SPSS software to analyze data and determine the relationship between variables. The data collection techniques used are questionnaires, literature study and observation. The data that has been collected will be analyzed in the form of quantitative numbers. The analysis technic used are Instrument Test, Descriptive Statistics, Classical Assumption Test and Hypothesis. The results that will be obtained later, the company will know whether there is a partial or simultaneous relationship to the variables studied. Conclusion Employee engagement and Job Satisfaction have a positive and significant influence on Turnover Intention.